The Effect of Green Banking and Financial Performance on The Firm Value in Banks Listed on the Indonesian Stock Exchange - Pungki Prastiwi; Rais Sani Muharrami (Masoem University, 2026)
This study investigates the impact of green banking and financial performance on firm value within the banking sector listed on the Indonesian Stock Exchange throughout the 2021-2024 period. A research design based on quantitative methods was employed secondary data obtained through banks' annual and sustainability reports. The empirical analysis was performed using panel data regression with the support of Eviews software. The findings reveal of green banking does not have a statistically significant impact on firm value, suggesting that the disclosure of green banking initiative continues to be perceived as regulatory compliance and has not yet become a key consideration for investors. In contrast, profitability (ROE) and revenue growth have a positive and significant impact on firm value, confirming that investors place greater emphasis on measurable financial performance when assessing banking firms. The evidence imply that green banking have not yet contributed directly enhance firm value due to its regulatory compliance nature, thus requiring more substantive implementation. At the same time, investors continue to prioritize financial performance in firm valuation.